Combination Strategies to Enhance the Efficacy of Antimicrobial Peptides against Bacterial Biofilms - Grassi, Lucia; Maisetta, Giuseppantonio; Esin, Semih; Batoni, Giovanna (Frontiers in Microbiology, 2017)
The great clinical significance of biofilm-associated infections and their inherent recalcitrance to antibiotic treatment urgently demand for the development of novel antibiofilm strategies. In this regard, antimicrobial peptides (AMPs) are increasingly recognised as a promising template for the development of antibiofilm drugs. Indeed, owing to their main mechanism of action that relies in the permeabilization of bacterial membranes, AMPs exhibit a strong antimicrobial activity also against multidrug-resistant bacteria and slow-growing or dormant biofilm-forming cells and are less prone to induce resistance as compared to current antibiotics. Furthermore, the antimicrobial potency of AMPs can be highly increased by combining them with conventional (antibiotics) as well as unconventional bioactive molecules. Combination treatments appear particularly attractive in the case of biofilms since the heterogeneous nature of these microbial communities requires to target cells in different metabolic states (e.g. actively growing cells, dormant cells) and environmental conditions (e.g. acidic pH, lack of oxygen or nutrients). Therefore, the combination of different bioactive molecules acting against distinct biofilm components has the potential to facilitate biofilm control and/or eradication. Aim of the present review is to highlight the most promising combination strategies developed so far to enhance the therapeutic potential of AMPs against bacterial biofilms. The rationale and beneficial outcomes of using AMPs in combination with conventional antibiotics, compounds able to disaggregate the extracellular matrix, inhibitors of signalling pathways involved in biofilm formation (i.e. quorum sensing) and other peptide-based molecules will be presented and discussed.